Savva, Petros G. - (:unkn) unknown (My University, 2026)
Dr. Petros G. Savva is currently working as a special teaching staff at the Department of Environmental Science and Technology of the Cyprus University of Technology. He teaches the undergraduate courses: Tools of Environmental Management (EST 201), Chemistry II (EST 106), Climate Change (EST 404) and Chemistry I and II laboratories (EST 101.E and EST 106.E). He also teaches the postgraduate lessons Systems and Tools of Sustainable Development (EST 502) and Air Pollution and Climate Change (EST 532). He obtained his BSc in Chemistry from the University of Cyprus, MSc from the University of Patras and PhD from the University of Cyprus. His research interests are in Environmental Catalysis (NOx, CO, HC and SOx de-pollution) from stationary and mobile sources, Carbon Nanotubes synthesis, Benzene Hydrogenation in Gasoline, and hydrogen production and use as an energy carrier. He has received several honorary awards and distinctions at a national and international level. Dr. Savva has 15 refereed scientific publications in international journals, more than 30 refereed conference presentations and has 4 European and International patents.
Keywords: chemistry; energy; engineering; environmental